2019
DOI: 10.1007/s12035-019-01776-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hypothalamic MCT4 and MCT1–MCT4 Expressions Affects Food Intake and Alters Orexigenic and Anorexigenic Neuropeptide Expressions

Abstract: Feeding behavior regulation is a complex process, which depends on the central integration of different signals, such as glucose, leptin, and ghrelin. Recent studies have shown that glial cells known as tanycytes that border the basal third ventricle (3V) detect glucose and then use glucose-derived signaling to inform energy status to arcuate nucleus (ARC) neurons to regulate feeding behavior. Monocarboxylate transporters (MCT) 1 and MCT4 are localized in the cellular processes of tanycytes, which could facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…In turn, their elongated processes project toward the arcuate nucleus (ARC), where feeding-regulating neurons reside 10 , suggesting that tanycytes could convey metabolic signalling to ARC neurons. Supporting this intercellular communication, we have shown that disruption of several tanycyte proteins involved in glucose metabolism, including GLUT2 11 , GK 12 , and MCT1-4 13 , 14 , increase food intake in rats. This led us to propose that glucose from the CSF is taken by tanycytes using GLUT2, which is then metabolized to lactate with the participation of GK.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…In turn, their elongated processes project toward the arcuate nucleus (ARC), where feeding-regulating neurons reside 10 , suggesting that tanycytes could convey metabolic signalling to ARC neurons. Supporting this intercellular communication, we have shown that disruption of several tanycyte proteins involved in glucose metabolism, including GLUT2 11 , GK 12 , and MCT1-4 13 , 14 , increase food intake in rats. This led us to propose that glucose from the CSF is taken by tanycytes using GLUT2, which is then metabolized to lactate with the participation of GK.…”
Section: Introductionmentioning
confidence: 64%
“…To evaluate the role of lactate and βHB over hypothalamic neuronal activity, we measured the expression of feeding-controlling neuropeptides in hypothalamic cultures containing mainly neurons by RT-qPCR (Figure 2 A), as prevoulsy done 11 , 14 , 18 . These cultures were maintained in 1 mM glucose and then we measured changes in neuropeptide mRNA levels 2 h post-stimulation as a consequence of neuropeptides released in response to different concentrations of glucose, lactate, and βHB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenoviral vectors were employed to express shRNAs against Mct1 [66,67], Mct4 [67], Gk [68], Glut2 [69], and Glut6 [70], driven by a human H1 promoter. These studies provided evidence that tanycytes are involved in the transport and metabolism of glucose as well as in metabolic sensing in the MBH.…”
Section: Viral Constructs To Manipulate Tanycytesmentioning
confidence: 99%
“…These studies provided evidence that tanycytes are involved in the transport and metabolism of glucose as well as in metabolic sensing in the MBH. A knockdown of the glu- [66,67]. It has been suggested that neurons of the MBH can sense the energy status of tanycytes as reflected by extracellular lactate concentrations [71].…”
Section: Viral Constructs To Manipulate Tanycytesmentioning
confidence: 99%